Meneguhkan Jiwa Kebangsaan Generasi Muda Melalui Penguatan Wawasan Kebangsaan Pada Peserta Didik Di SMK Tridharma Gorontalo - Ngiu, Zulaecha; Al Hamid, Saleh; Sahi, Yayan (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
The development of the digital era has brought new challenges to the understanding of national insight, particularly among students. As access to information becomes increasingly open, the potential for bias and disorientation regarding national values also rises, especially when not accompanied by adequate knowledge. In response to this condition, this community service activity was carried out with the aim of reaffirming the spirit of nationalism among the younger generation by strengthening their understanding of national insight. The target of this activity was the students of SMK Tridharma, Universitas Negeri Gorontalo, involving 33 students and 2 speakers. The method used included participatory and educational approaches, beginning with coordination and initial observation stages, followed by the preparation of materials based on student needs, and culminating in the main activity implementation. The materials provided emphasized the introduction of national identity, the fundamental values of the state, the meaning of national symbols, the importance of unity, tolerance, and diversity. The results of this service activity showed an increase in students’ understanding of national values and the emergence of collective awareness regarding the importance of preserving national integrity. In addition, communicative and interactive delivery methods such as dialogic lectures, group discussions, and value simulations proved effective in enhancing active student participation and making the material easier to understand. This activity also offered space for critical reflection, allowing students to connect national insight with the challenges of the digital era that they face. Thus, this community service underscores the importance of an educational approach that is applicable, value-based, and dialogic in shaping a strong sense of nationalism in the younger generation. This becomes a relevant and adaptive strategy for addressing the dynamics of social change in today’s digitalization era.